Idiosyncratic volatility puzzle: The role of assets' interconnections - Roberto Calogero Panzica (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
The paper investigates the determinants of the idiosyncratic volatility puzzle by allowing linkages across asset returns. The first contribution of the paper is to show that portfolios sorted by increasing indegree computed on the network based on Granger causality test have lower expected returns, not related to idiosyncratic volatility. Secondly, empirical evidence indicates that stocks with higher idiosyncratic volatility have the lower exposition on the indegree risk factor.
urn:nbn:de:hebis:30:3-472406
Keywords: G10; G12; 330; Idiosyncratic volatility puzzle; Networks; Expected Returns; Granger Causality